The Association Between Prenatal Exposure to Antidepressants and Autism: Some Research and Public Health Aspects - Kapra, Ori; Rotem, Ran; Gross, Raz (Frontiers in Psychiatry, 2020)
Use of antidepressants (ADs) in general, and pregnant notwithstanding, has been increasing globally in recent decades. Associations with a wide range of adverse perinatal and childhood outcomes following prenatal ADs exposure have been observed in registry-based studies, with Autism Spectrum Disorders (ASD) frequently reported. Studies using animal models, sibling analyses, and negative control approaches, have linked dysfunctional serotonin metabolism with ASD but did not convincingly tease apart the role of maternal mental health from that of ADs. As work to decipher the nature of the AD-ASD association continues, this review raises some public health concerns pertaining to a hypothetical conclusion that this association is causal, including the need to identify specific gestation periods with higher risk, the importance of precise assessment of the ASD potential prevention that might be attributed to AD discontinuation, and of the estimation of risks associated with prenatal exposure to untreated depression.